Predictive role of psychological capital and perceived organizational support on innovative work behavior among higher education teachers of Pakistan - Maria Wahid; Nadia Ayub (Universidad de Deusto, 2024)
The current study aimed to determine the predictive role of Psychological Capital (PsyCap) and Perceived Organizational Support (POS) on Innovative Work Behavior (IWB) among higher education teachers of Pakistan. A sample of 200 higher education teachers was recruited from various private and public sector institutes across Pakistan. The analysis revealed significant relationship between psychological capital and innovative work behavior (r= .700); and; perceived organizational support and innovative work behavior (r= .305). Also, psychological capital and perceived organizational support were found to be strong predictors of innovative work behavior (R= .700). In conclusion, when teachers possess psychological capital as their personal resource and perceived organizational support as social resource at workplace; they are more likely to demonstrate innovation into their work behavior. Received: 10 March 2023 Accepted: 28 November 2023